2019
DOI: 10.1088/1748-9326/ab1e75
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the climatic drivers of US agricultural yields

Abstract: Understanding the climatic drivers of present-day agricultural yields is critical for prioritizing adaptation strategies to climate change. However, unpacking the contribution of different environmental stressors remains elusive in large-scale observational settings in part because of the lack of an extensive long-term network of soil moisture measurements and the common seasonal concurrence of droughts and heat waves. In this study, we link state-of-the-art land surface model data and finescale weather inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
114
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(128 citation statements)
references
References 36 publications
11
114
0
3
Order By: Relevance
“…Underlying our statistical framework is the assumption that moisture availability influences yield variability similarly from May to July. Field-level studies have shown that certain growth stages (for example, tasselling and ear formation) are more sensitive to water stress 1,23 , although the general conclusions of this study do not change on the basis of the summertime months selected ( Supplementary Table 3).…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…Underlying our statistical framework is the assumption that moisture availability influences yield variability similarly from May to July. Field-level studies have shown that certain growth stages (for example, tasselling and ear formation) are more sensitive to water stress 1,23 , although the general conclusions of this study do not change on the basis of the summertime months selected ( Supplementary Table 3).…”
Section: Methodsmentioning
confidence: 54%
“…The inference of moisture-mediated exposure to damage from temperature is consistent with previous studies. Exposure to high temperatures has been found to cause amplified yield damage under conditions of low water availability 13,18,23 . Conversely, well-irrigated fields show little sensitivity to high atmospheric temperature 8,12,[15][16][17] .…”
mentioning
confidence: 99%
“…Ortiz-Bobea et al (2019) similarly finds that somewhat drier late-season conditions are beneficial for corn. 12 Using Gibbs sampling across four parallel chains, convergence is achieved quickly and analyzed using theGelman and Rubin (1992) potential scale reduction factor.…”
mentioning
confidence: 89%
“…One exception isOrtiz-Bobea et al (2019), who use detailed information on soil moisture from land surface model data from the North American Land Data Assimilation System. Their analysis of corn yields finds no statistically significant difference in mean climate change impacts between traditional models that use season-long temperature and precipitation and their proposed model of intra-seasonal temperature and soil moisture.…”
mentioning
confidence: 99%
“…However, to achieve the same going forward, we are faced with a two‐pronged challenge: (1) a plateauing rate of increase in grain yield across crops (Iizumi et al , ; Zhao et al , ); and (2) increasing intensity and frequency of harsh climatic conditions during the crop growth period (Zampieri et al , ; Pfleiderer et al , ). Among the climatic factors, a rapid increase in temperature is considered to be a primary factor affecting crop yields negatively (Ortiz‐Bobea et al , ). Temperatures above the critical threshold, termed as ‘heat stress’ can vary across crop growth and developmental stages, impacting different physiological processes ultimately reducing grain yield (Djanaguiraman et al , ).…”
Section: Introductionmentioning
confidence: 99%